Transcriptional Regulation of NK Cell Development by mTOR Complexes - Yang, Chao; Malarkannan, Subramaniam (Frontiers in Cell and Developmental Biology, 2020)
The mechanistic target of Rapamycin (mTOR) is indispensable for multiple cellular processes. The unique roles of mTOR complex 1 (mTORC1) or mTOR2 in regulating immune functions are emerging. NK cells are the major lymphocyte subset of innate immunity, and their development and effector functions require metabolic and transcriptomic reprogramming. Conditionally disrupting the formation of mTORC1 or mTORC2, impair the development of NK cells. Single-cell transcriptomic profiling of NK cells reveals that mTORC1 dictates the transcriptional programs required for the early developmental progression by upregulating Eomesodermin and T-bet. While the mTORC2 via T-bet to suppresses FoxO1, and thereby to complete the terminal maturation of NK cells. Here, we summarize the novel transcriptomic regulation employed by mTOR complexes during the development and functions of NK cells.